A SCIENTIFIC GREEDINESS IN HAWTHORNE’S ‘RAPPACCINI’S DAUGHTER’ (One Possible Interpretation of The Theme) - Murti Heruri (Universitas Stikubank (UNISBANK) Semarang, 2011)
Rappaccini’s Daughter is a story which was written by Nathaniel Hawthorne in 1844. Its principal setting is a fantastic garden filled with lush vegetation and poisonous flowers, in the center of which is a broken fountain. This story is replete with symbols and symbolic allusions. However, like other literary works, the story has an “empty space”. This paper is intended to invite the readers to one of the possible interpretations of the theme of this particular work of Hawthorne to fill that “empty space”. Man is superior to any other creatures. He has the capacity to learn and to develop himself. But, if “… he cares infinitely more for science than for mankind” and “if the head and heart are separated and the scientific functions alone, what price must the scientist pay?” The answer is the destruction to the life of mankind. Key words: intelligence, greediness, destruction